Development of Problem-based Learning online Model with the Support of Smart Mentoring System to Enhance Analysis Thinking Ability for Undergraduate Students - Kiangkhwa, Thirasak; Teemueangsai, Sanit; Songsanit, Songsak (Journal of Education Rajabhat Maha Sarakham University, 2023)
The purposes of this research were to: 1) develop a learning model by using problem-based online with the support of smart mentoring system for enhancing analytical thinking for bachelor’s degree student and 2) assess a learning model by using problem-based online with the support of smart mentoring system for enhancing analytical thinking for bachelor’s degree student. The research was conducted with mixed methods. The sample groups using the purposive sampling technique were: 1) 7 experts in problem-based learning, teaching through the network, smart mentoring system, psychology, and teaching of enhancing analytical thinking and 2) 5 qualified scholars in problem-based learning, teaching through the network, smart mentoring system, psychology, and teaching of enhancing analytical thinking. The research tool was an in-depth interview form. and model assessment form The statistics used in data analysis were content analysis, percentage, mean and standard deviation. The results showed that 1) the results of the development of a problem-based learning model as an online learning platform with support for learning. Smart mentor system to promote analytical thinking for undergraduate students It consists of two main components as follows: component 1 system section consists of 6 core modules: (1.1) instructor module (1.2) learners module (1.3) problem–based learning module (1.4) smart mentoring module (1.5) learning resource module and (1.6) assessment module: The second element is the user section. It consisted of 2 groups of users: (2.1) learners (2.2) instructor and 2) the appropriateness of learning model by using problem based online with the support of smart mentoring system for enhancing analytical thinking for bachelor’s degree student was at a very reasonable level.